“This is no way to tell a story”: Literary discourse making its way through the walled states of contemporaneity - Gonçalves, Davi (Revista Interfaces, 2017)
The object of this study is comprised by Stephen Leacock’s (1869-1944) novel Sunshine Sketches of a Little Town (1912). Through the advent of humour, the narrative gives readers an opportunity to reflect upon Mariposa, the fictional town where all events in the story take place, as a setting almost lost in space and time. My objective in this article is to investigate if, how, and why Mariposa is lost in space and time, attentive to the idea of individual versus collective identity and of local values versus universal ones. Cognisant that I am grappling with a narrative from the Early XX century Canada, I take such background into account for reflecting upon the epistemological contributions of the story as constructed by an unreliable narrator, as well as to raise the hypothesis that the novel might still have much to say to contemporary Brazilian readers. DOI: 10.5935/2179-0027.20170013